2014
DOI: 10.1021/jm401951t
|View full text |Cite|
|
Sign up to set email alerts
|

GPR103 Antagonists Demonstrating Anorexigenic Activity in Vivo: Design and Development of Pyrrolo[2,3-c]pyridines That Mimic the C-Terminal Arg-Phe Motif of QRFP26

Abstract: GPR103, a G-protein coupled receptor, has been reported to have orexigenic properties through activation by the endogenous neuropeptide ligands QRFP26 and QRFP43. Recognizing that central administration of QRFP26 and QRFP43 increases high fat food intake in rats, we decided to investigate if antagonists of GPR103 could play a role in managing feeding behaviors. Here we present the development of a new series of pyrrolo[2,3-c]pyridines as GPR103 small molecule antagonists with GPR103 affinity, drug metabolism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Therefore, effects of chronic blockade of QRFP signaling might have complex impact on animals’ body weight homeostasis. Recently, a GPR103 antagonist was shown to acutely decrease food intake in male mice[31]. But long-term effects of QRFP blockade on body weight or other phenotypes have remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effects of chronic blockade of QRFP signaling might have complex impact on animals’ body weight homeostasis. Recently, a GPR103 antagonist was shown to acutely decrease food intake in male mice[31]. But long-term effects of QRFP blockade on body weight or other phenotypes have remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the IC 50s of the latter compounds in radiobinding assays remain in the same range, that is, IC 50 = 40 nM for compound 10 and IC 50 = 280 nM for compound 11 compared with IC 50 = 70 nM for compound 5. Of note, the IC 50 for compound 5 measured by Georgsson et al (2014) is 10 times higher than the IC 50 for this compound reported in the original patent (IC 50 = 6.1 nM) (Haga et al, 2010a). Preclinical tests revealed for the first time an effect of a QRFP receptor antagonist: in a 3 day automated food intake measurement study, compound 10 ( Figure 11) provoked a significant and dose-dependent reduction on food intake compared to vehicle-treated animals (Georgsson et al, 2014).…”
Section: Figurementioning
confidence: 67%
“…The conformation of 11 used in this superimposition is only 0.8 kcal·mol −1 higher than the lowest energy conformation of 11 identified after optimization by quantum mechanics. These observations suggest that the antagonists designed by Georgsson et al () mimic the C‐terminal Arg 25 –Phe 26 residues of 26RFa/QRFP.…”
Section: Rfa/qrfp Receptor(s)mentioning
confidence: 80%
See 2 more Smart Citations